JIZZAKH OASIS IS ABOUT THE TRADITIONS ASSOCIATED WITH THE MARRIAGE WEDDING OF UZBEKS (Spectrum Journal of Innovation, Reforms and Development, 2022)
Uzbeks, like other peoples, are covered with various rituals from the beginning to the end of human life. Events that are held in connection with important turning points in human life are called family rituals. Family and family rituals are transmitters and successors of ethnic cultural and household traditions. Birthdays, namings, cradles and first belly hair removal, first steps, boys and girls going to school for the first time, birthdays, graduations, weddings, silver, gold and diamond weddings, retirement celebratory celebrations such as observances are unforgettable events in human life.